A Field-Relevant Concentration of the Insecticide Imidacloprid Affects Grooming, Locomotion, and Longevity in the Biological Control Agent Spalangia endius (Hymenoptera: Pteromalidae). Issue 3 (22nd April 2020) - Burgess, Edwin R; King, B H
Abstract: Foreign materials like insecticides may increase grooming in insects; and generally, grooming may be expected to reduce effects of insecticides, but this may not be the case when grooming involves the mouth and hence a risk of ingestion. To examine this, female Spalangia endius, a wasp that parasitizes filth fly pupae, were exposed to a surface coated with a low concentration of imidacloprid or not. Their mouthparts were sealed or not to determine whether sealing is a useful method for examining effects of mouth grooming. Wasps mouth-groomed more frequently while exposed to imidacloprid than when not. However, imidacloprid did not increase the number of times that a wasp groomed the rest of her body, and this was true regardless of whether or not her mouthparts were sealed. While exposed to imidacloprid, wasps spent less time locomoting only if their mouthparts were not sealed. Having been exposed to imidacloprid also decreased subsequent longevity, from 9 to 7 d. These effects of imidacloprid on grooming, locomotion, and longevity occurred despite exposure being for just 5 min and to only 2% of the amount that will be present in an area immediately after house fly baits are scattered at their recommended coverage. This is such a low amount that, with 48 h of constant exposure, mortality of these wasps is only 10%. Having mouthparts sealed decreased locomotion and longevity regardless of exposure to imidacloprid. Thus, sealing mouthparts is not useful for measuring effects of mouth grooming.